2023
DOI: 10.3390/children10081408
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Trust in Online Social Interactions: A Qualitative Exploratory Study

Elisa Colì,
Marinella Paciello,
Ernestina Lamponi
et al.

Abstract: Social media have become increasingly embedded in adolescents’ daily lives. Although these contexts have been widely studied, how trust in online relationships is built among adolescents is still an unexplored issue. By adopting the theoretical socio-cognitive model of trust, this study aims to explore the components of online trust as far as today’s teenagers are concerned. The study involved 10 adolescents aged between 12 and 18 (M = 15.5). The data were collected using individual semi-structured, audio-reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Another important aspect of SNS use by young people is how they use them. A qualitative exploratory study on 10 adolescents between 12 and 18 showed that teens appeared conscious of choosing who they trust in online social interactions (Colì et al, 2023). The study revealed that adolescents tend to interact with peers they have already known in real life or online communities with which they identified similarities in interest, age, ways of thinking, and things they are passionate about (Colì et al, 2023).…”
Section: Adolescents' Ways Of Using Snsmentioning
confidence: 98%
See 2 more Smart Citations
“…Another important aspect of SNS use by young people is how they use them. A qualitative exploratory study on 10 adolescents between 12 and 18 showed that teens appeared conscious of choosing who they trust in online social interactions (Colì et al, 2023). The study revealed that adolescents tend to interact with peers they have already known in real life or online communities with which they identified similarities in interest, age, ways of thinking, and things they are passionate about (Colì et al, 2023).…”
Section: Adolescents' Ways Of Using Snsmentioning
confidence: 98%
“…During the developmental period, adolescents experience biological, psychological, and social changes that come with various developmental tasks, for example, developing personal identity, forming strong identification with peers, and establishing social autonomy (Christie & Viner, 2005). In general, past studies have discussed the interplays between SNS use and adolescents' psychosocial development, for example., identity development (Papacharissi, 2011;Spies Shapiro & Margolin, 2014;Valkenburg et al, 2005;Yang et al, 2022), and formation and maintenance of interpersonal relationships with peers or close others (Boyd, 2014;Colì et al, 2023;Davis, 2012;Spies Shapiro & Margolin, 2014).…”
Section: Sns Use and Adolescence Developmentmentioning
confidence: 99%
See 1 more Smart Citation